2016
DOI: 10.5430/ijhe.v5n2p63
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Attitudes for Changing a University’s Core and Structure

Abstract: America's universities and colleges are examining additional ways to raise student enrollment following government reductions in educational funding. Faculty were surveyed regarding their opinions of an administrative proposal to change the status of their commuter university, a school without any on-campus student housing, from teaching traditional semester length courses to predominately online and compressed courses. Results indicated that although younger faculty were willing to teach lower level courses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Interestingly, faculty reticence remains a barrier to both online and accelerated course offerings. A recent survey of faculty opinions at a state flagship university revealed that while younger faculty were willing to teach select courses online, senior faculty viewed teaching online and teaching in an accelerated format unfavorably [14].…”
Section: Accelerated Learning Researchmentioning
confidence: 99%
“…Interestingly, faculty reticence remains a barrier to both online and accelerated course offerings. A recent survey of faculty opinions at a state flagship university revealed that while younger faculty were willing to teach select courses online, senior faculty viewed teaching online and teaching in an accelerated format unfavorably [14].…”
Section: Accelerated Learning Researchmentioning
confidence: 99%
“…Online learning is often thought to be a panacea towards driving larger student enrollment and subsequent tuition revenue at lower costs from faculty and overhead costs (Gilpin et al, 2015). However, adding this modality to the educational model can lead to faculty dissatisfaction as opposed to teaching in a face-toface modality (Krug et al, 2016) and low student persistence and grades (Xu & Jaggars, 2013).…”
Section: Theme 3: Diversification Of Revenue Streamsmentioning
confidence: 99%
“…This flexibility allows these institutions to be nimble and properly adjust their lineup of degree offerings accordingly (Gilpin et al, 2015), a characteristic which escapes certain small, nonprofit colleges and universities. However, online learning, thought to be a panacea towards driving larger student enrollment and subsequent tuition revenue at lower costs from faculty and overhead costs (Gilpin et al, 2015), can lead to faculty dissatisfaction as opposed to teaching in a face-to-face modality (Krug et al, 2016) and low student persistence and grades (Xu & Jaggars, 2013). Related to increased classroom enrollments, a guiding principle for FPCs, when utilized by non-FPCs the result is poor student outcomes leading to student dissatisfaction (Cheng, 2011) and a lower quality educational experience (Wolff et al, 2014).…”
Section: Challenges For Small Tertiary Institutionsmentioning
confidence: 99%
See 1 more Smart Citation